Zoo inverso : an investigation of landscape architecture as an instrument to convey experience, habitat and beauty within a zoological garden enclosure - Prinsloo, Johan Nel (University of Pretoria, 2015)
Dissertation (ML(Prof))--University of Pretoria, 2014.